Analisis Wacana Kritis Model Sara Mills pada Berita “Isu Perselingkuhan Jule, Na Daehoon: Saya Kuat Demi Anak-Anak” di detik.com - Zalfa Nur Munifah; Tsavalia Desla Gunlista Putri (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
This study analyzes the news text on the online mass media detik.com titled "Jule's Infidelity Issue, Na Daehoon: I am strong for the sake of the children" using Sara Mills' Critical Discourse Analysis model. This research aims to reveal how the discourse of infidelity is constructed in media texts thru subject and object positioning, how character representation is displayed, how the reader's position is directed, the use of narrative structure, and the social context and gender ideology underlying the construction of this discourse. The research method used is a qualitative descriptive method with the data source being a news text published on detik.com. Data collection techniques were carried out thru document study by carefully reading and recording linguistic units relevant to the research focus, while data analysis techniques used Sara Mills' Critical Discourse Analysis model. The research findings indicate that Na Daehoon is positioned as the dominant subject, possesses voice legitimacy, and is positively represented as a strong and responsible male figure. Conversely, Jule is positioned as the object of news coverage, receiving no opportunity for clarification and being implicitly represented as the problematic party. Additionally, the narrative structure and language choices used in the news text also guide readers to build sympathy toward the male subject. The findings indicate that the analyzed news coverage is not neutral, but rather tends to reproduce patriarchal gender ideologies that could potentially influence society's perception of women in cases of infidelity.